Foreign direct investment and poverty in sub-Saharan African countries: The role of host absorptive capacity - Sodiq Arogundade; Mduduzi Biyase; Hinaunye Eita (Cogent Economics & Finance, 2022)
This study examines the role of human capital and institutional quality on the impact of foreign direct investment (FDI) on poverty in sub-Sahara Africa (SSA). In achieving this, a balanced panel of 30 SSA countries from 1996 to 2018 was explored using fixed-effect instrumental regression, fixed effect panel threshold model, and the heterogenous Granger-causality test. There are three main important findings from this empirical study: (1) FDI does not have a direct impact on the incidence and intensity of poverty. (2) the impact of FDI is contingent on the absorptive capacity of the host country. The study further reveals that FDI will alleviate poverty conditions if interacted with human capital and institutional quality at a given threshold. (3) bidirectional causality between FDI and poverty. This study recommends that in addition to FDI's promotional policies, governments of SSA countries need to improve investment in human capital. It is also important for SSA countries to embark on public sector reforms, as investments do not thrive in an environment characterized by high corruption or political instability.
Keywords: F23; I30; E24; E02; 330; Poverty; Foreign direct investment; Absorptive capacity; Instrumental regression; Fixed-effect panel threshold model; heterogenous Granger-causality test; subSaharan African countries